Penyuluhan Pemberian Pupuk NPK Phoska untuk Tanaman Bayam Merah di Polybag pada Kelompok Ibu –Ibu PKK RT 23 Kelurahan Pasir Putih Kota Jambi - Nasution, Hasriati; Yusfaneti, Yusfaneti; Saad, Asmadi; Mulyati, Sri (WIDA Publishing, 2025)
The Red Spinach plant (Amaranthus sp.) has the characteristics of a soft stem, round in shape, growing straight up, unisexual compound type flowers, and generally green in color. This plant, which can grow throughout the year both at low and high altitudes, is known to have high iron, vitamin A, vitamin C, vitamin B and calcium. In order for Red Spinach plants to show red and fresh leaf growth, one of the requirements is the fulfillment of nutrients for plants by applying NPK Phonska fertilizer. This fertilizer promotes healthy root development, enhances greenness and freshness, and supports the formation of large leaves with sturdy stems. This community service aims to improve the skills of women in the PKK group RT 23, Pasir Putih Village, Jambi City, in planting red spinach so that they can thrive. The activity included two stages: delivering material and conducting field practice. The implementation team provided red spinach seeds, NPK Phoska fertilizer, polybags, soil media, water, machetes, hoes, and buckets. Post training, the participants' knowledge increased and is expected to be applied to produce red spinach that grows optimally.